Supporting Transition in Coal Regions : A Compendium of the World Bank’s Experience and Guidance for Preparing and Managing Future Transitions - World Bank (World Bank, Washington, DC, 2021)
This report outlines structural changes (adjustments) in the coal sector of eight countries in different regions of the world over the last 50 years that resulted from a transition away from coal to other energy sources in those regions. The countries are chosen because they provide a rich set of experiences from which lessons can be learned to help governments prepare for and manage a transition away from coal. Coal sector adjustment received World Bank support in four of the countries: Russia, Ukraine, Poland, and Romania. Broader observations are provided on four other countries where the World Bank was not providing support: namely, the United Kingdom and the Netherlands, where adjustment started in the 1960s; the United States, where employment adjustment started in the 1980s; and China, where adjustment started in the 1990s.